Leadership Style Based on Competency and Talent Management in Higher Education In Responding to â€œIndependent Campusâ€ Policy - Mulyadi Suhardi; Wentry Merdiani (Universitas Dharma Wacana, 2022)
This research is aimed at knowing the effect of leadership style based on competency and talent management in higher educationÂ in responding to â€œIndependent Campusâ€ policy as well as the elements of changes that occur in the whole system of the higher education institution. The methods used a systematic secondary data searching, meta analysis and survey. There are 100 respondents are selected using simple random sampling. The analysis procedure is path analysis. The research findings show that there are threeÂ main category changes in IndonesianÂ higher education institution concerning with first. learning model and student affairs; second, science and technology; third, higher education institutions and their resources. Further more,Â leadership style based on competency and talent management affects significantly on response to the â€œIndependent Campusâ€ policyÂ both partially and simultaneously. In conclusion, leadership style based on competency and talent management can contribute in enhancing the capabilities of the leaders among the higher institutions in Indonesia to respond the changes relating to the government policy of Independent Campu